Implementasi Algoritme A* Pada Software Defined Network Untuk Mencari Jalur Terpendek - Al Aziiz Burhanudin Faidzin Labay; Primantara Hari Trisnawan; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Software Defined Network (SDN) is a new networking paradigm that decouples or separates the control plane from the data plane. The Software Defined Network makes it easy to develop and experiment new protocols, easy to manage and adapting in infrastructure changes. The A* algorithm implemented in ONOS Controller with Abilene topology works well. Using A* Algorithm can produce the shortest path that is calculated from the real distance with an average time to make a path is 15,766 ms. The results of testing is showing that the average value of throughput and packet loss at 5 clients is 100.2 Mbps and packet loss is 2.1%, for 7 clients is 92.5 Mbps with packet loss of 3.9% and 72.06 Mbps with 7.5% packet loss for 9 clients. The average delay value is 0.081 ms. The A* Algorithm implemented in the ONOS Controller also works well when there is a fail link with an average convergence time value is 20,773 ms.